2021
DOI: 10.19087/jveteriner.2021.22.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Colorimetric-Based Rabies Postvaccination Antibody Titer Detection Using Elisa Reader and Mobile Phone Camera

Abstract: Rabies is an infectious disease, zoonotic, caused by virus from the genus Lyssa virus and generally transmitted by the bite of rabid animal, especially rabies infected dog. Rabies is preventable but is always fatal to humans if the central nervous system (CNS) is infected. Vaccination has been used as one of rabies prevention programmed. A total of 83 samples were tested using an Indirect ELISA (Enzyme Linked Immunosorbent Assay) to identify post-vaccination rabies antibody titer. Antibody titres correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on the standard curve, it can be observed that the y-axis represents the reading results from the ELISA reader in the form of absorbance values, while the x-axis represents the concentration values of the standard solution. According to [15], the R-value will indicate a strong relationship when it is close to -1 for a negative correlation or +1 for a positive correlation. Figure 1 shows that the R 2 value is 0.9917, indicating a strong positive relationship between concentration and absorbance.…”
Section: Histamine Level Testing Resultsmentioning
confidence: 99%
“…Based on the standard curve, it can be observed that the y-axis represents the reading results from the ELISA reader in the form of absorbance values, while the x-axis represents the concentration values of the standard solution. According to [15], the R-value will indicate a strong relationship when it is close to -1 for a negative correlation or +1 for a positive correlation. Figure 1 shows that the R 2 value is 0.9917, indicating a strong positive relationship between concentration and absorbance.…”
Section: Histamine Level Testing Resultsmentioning
confidence: 99%